Analysis of three disinfectants after immersion of irreversible hydrocolloid and ZOE paste impressions. - Sheila R. S. Porta; Vanderlei L. Gomes; Luiz A. Pavanin; Carla C. B. Souza (Universidade Estadual de Campinas, 2015)
This investigation sought to analyze 3 disinfectants: 0.5% chlorhexidine, 2% glutaraldehyde, and 1% sodium hypochlorite after immersion of irreversible hydrocolloid and zinc oxide-eugenol paste impressions. Changes detected in the solutions could suggest alterations in the dental impressions, compromising their quality and negatively influencing treatment outcome. Forty-five irreversible hydrocolloid impressions (Jeltrate) made in aluminum stock impression trays (AG) as well as 45 irreversible hydrocolloid and 45 zinc oxide-eugenol paste (Horus) impressions made in auto polymerizing acrylic resin (AAR) trays (VipiFlash) were immediately immersed in 200mL of 0.5% chlorhexidine (Labfa), 2% glutaraldehyde (Glutaron II), or 1% sodium hypochlorite ( Miyako) solutions for 10, 30, and 60 minutes. After immersion the solutions were analyzed by visible ultraviolet spectroscopy and turbidimetry to verify possible alterations. Turbidimetry (registered in nephelometric turbidity units -NTU) results were subjected to Kruskal-Wallis and Mann-Whitney tests for statistical analysis (á=.05). An increase of absorption levels of all disinfectants was found after immersion of irreversible hydrocolloid impressions. This increase was proportional to time of immersion and absorption was higher for 0.5% chlorhexidine for the 3 time periods analyzed. Only 1% sodium hypochlorite presented statistically significant alterations after immersion of zinc oxideeugenol paste impressions.